Analisis Kinerja PT. Semen Tonasa Melalui Pendekatan Balanced Scorecard : Upaya Meningkatkan Daya Saing di Industri Semen - Mediaty, Mediaty; Usman, Asri; Pangraran, Fisca Mawa'; Nadhifa, Nisrinatul; Irianto, Laode Wijaya Bagus (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aimed to offer insights for management to enhance performance across various aspects to remain competitive in the cement industry. Methods: This study analyzed PT. Semen Tonasa's performance uses the balanced scorecard approach, covering finance, customers, internal business processes, and learning and growth. Data were gathered from companies’ financial statements and surveys of employees and customers. Resuts: Of the 14 performance indicators assessed, four exceeded standards, four met standards, and six were below standards. The overall performance was rated as sufficient, with 55.56% achievement, indicating no significant improvement from the previous year. Limitations: PT. Semen Tonasa needs to continue efforts to improve performance, especially in terms of financial aspects, employee productivity, and customer satisfaction, in order to be able to compete in the cement industry. In addition, the implementation of the baanced scorecard needs to be optimized to improve performance. Contribution: This research analyzes PT Semen Tonasa’s companies using a balanced scorecard approach and provides insights for improving company performance in the future.